Language Attitude and Language Choice in Bilingual Academic Learning Environment - Udiana Puspa Dewi; Criscentia Jessica Setiadi (Bina Nusantara University, 2018)
The objectives of this research were to observe the language attitude and factors determining language choice of English Department students of Bina Nusantara University. The observation carried out by exploring the motivation, language choice, and language practice of the English Department students. The data were collected through a questionnaire, which was designed to capture the students’ motivation in studying English, language choice, and practice. The result of this research shows that the English department students hold the positive attitude toward English, which are shown through the statement of the majority of the students who argue that English is an international language and offers more career opportunities. The two main factors determining the use of English are the role of the lectures and the English language exposure in the academic environment. This result is expected to provide a context to design an effective English learning process to encourage students in practicing the language.